The Role of Teachers in The Development of National Characters in Religion Based School: a Case Study In SD Muhammadiyah 3 Nusukan Surakarta Indonesia - Ardiansyah, Roy (Universitas Sebelas Maret, 2019)
The phenomenon of the spread of religious-based elementary schools in the community will certainly have an impact on the development of the Indonesian Human Resources Development Index. This includes efforts to strengthen the National Character. The purpose of this study is to describe the role of teachers in religion-based elementary schools in strengthening the national character of students. This research uses a qualitative approach. The subjects of this study were 37 students and teachers. Data collection techniques used in this study were participant observation, in-depth interviews, literacy studies, and questionnaires. Analysis of the data used is Miles and Huberman Interactive Analysis. The results showed that teachers have an important role in strengthening the Nationality Character in Religion-Based Primary Schools, namely (1) Teachers not only teach about concepts but also emulate them, (2) Provide effective communication media between students and parents, (3) and supervise every student's behavior